The Role of Language Laboratory in Improving the English Language Proficiency of Students at Pesantren Musthofawiyah Purba Baru - Nasution, Dina Syarifah; Agustina, Ria; Anggraini, Dewi; Juita, Novia; Ardi, Havid (Mau`izhah : Jurnal Kajian Keislaman, 2024)
The language laboratory plays a pivotal role in enhancing English language proficiency at Pesantren Musthofawiyah Purba Baru. Through a mixed-methods research approach, including quantitative analysis and qualitative insights, this study investigates the utilization patterns, effectiveness, challenges, and recommendations associated with the language laboratory. Findings reveal significant improvements in vocabulary acquisition, grammatical accuracy, oral fluency, and listening comprehension. Student testimonials highlight increased confidence and proficiency, while teacher perspectives emphasize innovative pedagogical strategies and technological resources. Challenges include resource constraints, curriculum integration, and cultural factors. Recommendations focus on infrastructure investment, curriculum alignment, and teacher training. Overall, language laboratories are instrumental in fostering linguistic empowerment and academic excellence, contributing to global citizenship and educational innovation.